Integrating SQ4R Technique with Graphic Postorganizers in the Science Learning of Earth and Space - Djudin, T.; Amir, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study examined the effect of integrating SQ4R reading technique with graphic post organizers on the studentsÃ¢â‚¬â„¢ Earth and Space Science learning achievement and development of metacognitive knowledge. The pretest-posttest non-equivalent control group design was employed in this quasi-experimental method. The sample which consists of 103 seventh grade of secondary school students of SMPN 1 Pontianak was drawn by using intact group random sampling technique. An achievement test and a questionnaire ofÃ‚Â Reading-Self Awareness were administered. The findings assert that there are significant difference of studentsÃ¢â‚¬â„¢ achievement (F=5.594, p Ã¢â‚¬Â¹ 0.05) and development of metacognitive knowledge (F= 13.906, p Ã¢â‚¬Â¹ 0.05) among groups after having received the three distinctive treatments. Integrating SQ4R reading technique with graphic post organizers reveals an effective impact on the academic achievement (ES= 0.69) and the metacognitive knowledge in reading text (ES = 0.48). It confirms that a science teacher has to execute and model metacognitive strategies intentionally.